Influencia de la aplicación de ozono (O3) en tres concentraciones en tres variedades de chocho (Lupinus mutabilis) desamargado disuelto en agua - Vargas Ortiz, Tatiana Monserrat (2019)
The present investigation was carried out in order to apply an ozone treatment (O3) in three varieties of chochos such as: (Andean, native and Peruvian) to evaluate the useful life of the uncorked chocho under the application of three ozone concentrations (O3) which were: 0.75 ppm; 0.92 ppm; and 1.10 ppm, dissolved in water. On the other hand, ozone has proven to be one of the best disinfectants, both for water, food, among others. A fundamental advantage of ozone in its disinfection process does not generate any type of chemical waste, as this gas is converted to oxygen naturally. The results obtained from the microbiological analyzes (Escherichia coli, aerobic mesophilic, molds and yeasts) were determined that the best treatment after ozone disinfection was a, b3 (Chocho native variety disinfected with an ozone concentration at 1.10 ppm) It was ideal for the execution of the next stage of the investigation. Bromatological analyzes were performed at treatment a b with the following parameters that were: (moisture, dry matter, protein, fat, ash, fiber, total carbohydrates, energy), which reported the following values of 74.13% humidity; 25.87% dry matter; 14.30% protein; 2.27% fat; 0.86% ash; 3.52% fiber; 8.44% total carbohydrates; and 111.39 Kcal / 100g energy respectively; taking as reference the Standard NTE INEN 2390: 2004 Legumes. Unclogged grain of chocho. Finally, the useful life of the best treatment a, b3 (Chocho native variety disinfected with an ozone concentration at 1.10 ppm) was determined considering that the storage temperature was (4-8 ° C), the useful life was evaluated every week obtaining a result of 28 days of product stability. This research will serve as a scientific basis for further research related to the subject, and will also contribute to the different sectors such as producers, small and large industries that are dedicated to the commercialization of the chocho, because with the increase of the useful life of the chocho It will help the different sectors to generate an increase in competition in the market and therefore their profits.